PS5:103 Costimulatory maker on cytotoxic cd8+ t-cells in patients with sle. (21st March 2018) - Oster, C; Wilde, B; Hübbers, K; Kribben, A; Witzke, O; Dolff, S
Abstract : Background: Systemic lupus erythematodes (SLE) is an autoimmune disease where T-cell dependent B-cell activation plays a crucial role. Costimulatory marker promote and inhibit immune responses after ligation. Here we analysed the marker BTLA (CD272), PD-1 (CD279), HLA-DR and HVEM on peripheral cyctotoxic T-cells. Patients and methods: 30 SLE-patients fulfilling the American College of Rheumatology (ACR) criteria für SLE and 14 healthy controls (HC) were enrolled. Whole blood staining was performed and samples were analysed by multi-colour flow cytometry. Disease activity was assessed by SLEDAI. Renal involvement was defined as biopsy proven lupus nephritis. Results: The expression of the costimulatory marker PD-1 is signifcantly increased on CD8 +T cells in SLE patients as compared to with healthy controls (31.3%±26.7% vs 15.63%±12.22%). We could not found a significant difference in the expression levels of the BTLA receptor on CD8 +T cells (72, 24%±15.33 vs 72.66%±9, 4%) in SLE patients as compared to with healthy controls. Also HLA-DR and HVEM was not significantly different expressed on CD8 +T cells in SLE. Conclusions: The costimulytory maker PD-1 is upregualted on cytotoxic T-cells in SLE. Further investigations are needed to elucidate the functional role of this pattern.